A Lingual Politic: Power and Resistance in Sacred, Secular, and Subaltern Narratives in an Age of Mass Incarceration. (1st January 2016) - Nikia Smith Robert
Abstract: This article submits that the confluence of language and power proliferate social strata and exacts violence on subaltern bodies in a punitive age of mass incarceration. I explore racialized social hierarchies in Judeo-Christian sacred texts and its relationship to secular texts that mark subaltern bodies for punishment. I argue that hegemonic scriptural economies perpetuate discursive violence that is evident in the imperial use of jurisprudence to warehouse latina/o bodies in a prison industrial complex. In response, proclamations of protest become the voice of victors to self-name, overcome silence and rewrite histories as authors of subaltern narratives of resistance. Keywords : Sacred texts, Legal texts, Social regulation, Subalternity, Racism, Narrative of resistance, Punishment, Mass Incarceration.